The Use of Culturally-Familiar Literature in the EFL Classroom - Ahmad, Sadaf Khalil (2013)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Sadaf Khalil Ahmad entitled, "The Use of Culturally-Familiar Literature in the EFL Classroom," May 2013. Thesis advisor is Dr. Khawlah Ahmed. Available are both hard and soft copies of the thesis.